PENGAWASAN PELESTARIAN HUTAN LINDUNG OLEH DINAS KEHUTANAN DAN PERKEBUNAN KABUPATEN INDRAGIRI HILIR - Siti Lusiah; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Surveillance of protected forests done to explore and assess the implementation of forest management, so that the goal can be achieved to the fullest and is a feedback for improvement or further refinement of forest management, local authorities also conduct surveillance of protected forest communities and individuals also play a role in monitoring the protected forest. The local government is also authorized to monitor, collect information and perform inspection supervision over the implementation of the protected forest. The condition of forests and protected forest areas, especially in Indragiri Hilir very poor condition of the mark with the increasing degradation, reduced investment in forestry, the low progress of plantation establishment, less uncontrolled illegal logging and illegal trade, economic decline within the community and around forests, increasing forest areas that are not conserved in both the government and society To analyze these problems the author uses the theory Manullang which is consistent with the theory that problem. This research is a descriptive qualitative approach, where data collection technique is a technique of observation and interviews with key informants as key informants. It can be concluded that the results of interviews and observation that has been done in the field with respect to the supervision of protected forest conservation has so far been implemented fairly well in accordance with the policies and regulations of the Department of Forestry and Agriculture in accordance with the duties and functions of each office. Human resources are not sufficient to the task of monitoring the implementation of the protected forest conservation that follow in the budget is not adequate to be allocated for personnel and forest conservation in Indragiri Hilir optimally. Keywords: Monitoring, Protection Forest Conservation, Department of Forestry and Plantation